Identification of odorant binding proteins and chemosensory proteins in Microplitis mediator as well as functional characterization of chemosensory protein 3 - Peng, Yong; Wang, Shan-Ning; Li, Ke-Ming; Liu, Jing-Tao; Zheng, Yao; Shan, Shuang; Yang, Ye-Qing; Li, Rui-Jun; Zhang, Yong-Jun; Guo, Yu-Yuan (PloS one, 2017)
Odorant binding proteins (OBPs) and chemosensory proteins (CSPs) play important roles in transporting semiochemicals through the sensillar lymph to olfactory receptors in insect antennae. In the present study, twenty OBPs and three CSPs were identified from the antennal transcriptome of Microplitis mediator. Ten OBPs (MmedOBP11-20) and two CSPs (MmedCSP2-3) were newly identified. The expression patterns of these new genes in olfactory and non-olfactory tissues were investigated by real-time quantitative PCR (qPCR) measurement. The results indicated that MmedOBP14, MmedOBP18, MmedCSP2 and MmedCSP3 were primarily expressed in antennae suggesting potential olfactory roles in M. mediator. However, other genes including MmedOBP11-13, 15-17, 19-20 appeared to be expressed at higher levels in body parts than in antennae. Focusing on the functional characterization of MmedCSP3, immunocytochemistry and fluorescent competitive binding assays were conducted indoors. It was found that MmedCSP3 was specifically located in the sensillum lymph of olfactory sensilla basiconca type 2. The recombinant MmedCSP3 could bind several types of host insects odors and plant volatiles. Interestingly, three sex pheromone components of Noctuidae insects, cis-11-hexadecenyl aldehyde (Z11-16: Ald), cis-11-hexadecanol (Z11-16: OH), and trans-11-tetradecenyl acetate (E11-14: Ac), showed high binding affinities (Ki = 17.24-18.77 μM). The MmedCSP3 may be involved in locating host insects. Our data provide a base for further investigating the physiological roles of OBPs and CSPs in M. mediator, and extend the function of MmedCSP3 in chemoreception of M. mediator.